1973
DOI: 10.1017/s0014479700023632
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis in Crosses of Theobroma cacao

Abstract: SUMMARYThis paper reports the heterotic pod production of three different crosses between a Nigerian local selection (N38) and three Trinidad Introductions (CF47, CF56 and CF207). The hybrids consistently outyielded the inbreds throughout the first 19 years of pod production. N38 × CF56 hybrid produced the highest number of pods per tree, closely followed by N38 × CF47 hybrid; while N38 × CF47 hybrid showed the best heterotic response. Pod production figures of (CD207)2 and (CD302)2, both double inbreds of N38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…They could be tested as parents of hybrids aiming to reduce variability in operational plantations and potentially exploit hybrid vigor in a more systematic way. A number of studies have shown a strong influence of dominance variance on cacao yield, supporting the dominance hypothesis for heterosis [ 15 , 53 , 62 65 ]. Additionally, a relationship between multivariate genetic divergence based on phenotypic traits with combining ability effects was reported in cacao, with the most divergent cultivar exhibiting high general combining ability, producing the best performing hybrids [ 66 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…They could be tested as parents of hybrids aiming to reduce variability in operational plantations and potentially exploit hybrid vigor in a more systematic way. A number of studies have shown a strong influence of dominance variance on cacao yield, supporting the dominance hypothesis for heterosis [ 15 , 53 , 62 65 ]. Additionally, a relationship between multivariate genetic divergence based on phenotypic traits with combining ability effects was reported in cacao, with the most divergent cultivar exhibiting high general combining ability, producing the best performing hybrids [ 66 ].…”
Section: Discussionmentioning
confidence: 83%
“…The use of inbred lines as parents of hybrids could minimize the problems associated with both, clonal propagation and interclonal hybrid variability, by consolidating the advantages of both deployment methods, i.e., seed propagation and capture of hybrid vigor. This was attempted since the beginning of hybrid breeding in cacao by searching for naturally inbred selections from local populations (e.g., Amelonado, Matina) [ 10 – 13 ], using partially inbred lines [ 11 , 13 – 15 ], looking for spontaneous haploids to be diploidized [ 16 ] and through the use of anther culture [ 17 – 19 ]. All these strategies ultimately try to overcome the challenge associated with the production of fully inbred parents in cacao by the traditional method of successive self-fertilizations, a lengthy process, given the long generation time in cacao (3–5 years/generation) and large experimental area required (commonly 9 m 2 /tree).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, as variedades diferem em percentagem de umidade, contribuindo para reduzir a efe tividade deste componente, como parâmetro discriminador (BARTLEY, 1967). Ainda assim, POUND (1932a, 1932b, 1933) (RUINARD, 1961;ATANDA, 1972a;ESKES et alii, 1977;ENGELS, 1983). Existe alta correlação entre o número de frutos produzidos e o peso total de sementes ú midas (GLENDINNING, 1963;ESQUIVEL & SORIA, 1967;ATANDA & TOXOPEUS, 1971;ATANDA, 1972a) e entre os primeiros e a pr� dução de sementes secas (ESQUIVEL & SORIA, 1967).…”
Section: Revisão De Literaturaunclassified
“…O sucesso do milho hibrido motivou a realiza ção de intensas pesquisas em outras espécies, em busca de respostas heter6ticas para caracteres de interesse. Na cul tura do cacau, diversos autores (RUSSEL, 1952;SORIA, 1964;OPEKE & JACOB, 1969;ATANDA & TOXOPEUS, 1971;REYES & PEREZ, 1971;ATANDA, 1972bATANDA, , 1973…”
Section: Com Respeito àS Correlações Genéticas Calcuunclassified